Na literarnem otoku Berte Bojetu - Zupan Sosič, Alojzija (Jezik in slovstvo, 1998)
The article discusses the thematically and formally rounded literary work of Berta Bojetu Boeta. Women, birds and violence are the nuclei of her poetic messages in the collections of poems Žabon (Male Frog, 1979), Besede iz hiše Karlstein (Words from the House of Karlstein, 1988) and the novels Filio ni doma (Filio is Not at Home, 1990) and Ptičja hiša (The Bird's House, 1995). These nuclei are linked into a horrifying circle of monotonous repetition and failed attempts to achieve harmonious coexistence, a circle permitting no one to get out. This makes Bojetu's writing a special "island" in Slovene literary tradition, which despite its female characters and frequent reflections on the role of women cannot be discussed only witin the framework of the so-called "women's literature".
Keywords: Bojetu, Berta; Slovene literature; slovenska književnost; slovenska proza; slovenska poezija; literarne študije